Lung transplantation in the Lung Allocation Score era: Medium‐term analysis from a single center. Issue 8 (15th June 2018) - Iyengar, Amit; Kwon, Oh Jin; Sanaiha, Yas; Eisenring, Christian; Biniwale, Reshma; Ross, David; Ardehali, Abbas
Abstract: In 2005, the Lung Allocation Score (LAS) was implemented as the allocation system for lungs in the US. We sought to compare 5‐year lung transplant outcomes before and after the institution of the LAS. Between 2000 and 2011, 501 adult patients were identified, with 132 from January 2000 to April 2005 (Pre‐LAS era) and 369 from May 2005 to December 2011 (Post‐LAS era). Kruskal‐Wallis or chi‐squared test was used to determine significance between groups. Survival was censored at 5 years. Overall, the post‐LAS era was associated with more restrictive lung disease, higher LAS scores, shorter wait‐list times, more preoperative immunosuppression, and more single lung transplantation. In addition, post‐LAS patients had higher O2 requirements with greater preoperative pulmonary impairment. Postoperatively, 30‐day mortality improved in post‐LAS era (1.6% vs 5.3%, P  = .048). During the pre‐ and post‐LAS eras, 5‐year survival was 52.3% and 55.3%, respectively ( P  = .414). The adjusted risk of mortality was not different in the post‐LAS era ( P  = .139). Freedom from chronic lung allograft dysfunction was significantly higher in the post‐LAS era ( P  = .002). In this single‐center report, implementation of the LAS score has led to allocation to sicker patients without decrement in short‐ or medium‐term outcomes. Freedom from CLAD at 5 years is improving after LAS implementation.